High-efficiency halogen-free flame-retardant HIPS material and preparation method thereof

CN116218121BActive Publication Date: 2026-10-30JIANGSU HAIJU NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310094399.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2026-10-30
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

[0003]但是,HIPS较低的氧指数(18%)导致它极其易燃,而且燃烧时还会出现熔滴现象,因此限制了HIPS在许多场合的应用

Benefits of technology

[0031]1、本发明使用了一种新颖的阻燃体系,具体的是结合膨胀型阻燃剂(IFR)+协效阻燃剂+离子液体+PPO,具体的阻燃机理为多方面的组合:①气相阻燃机理,膨胀型阻燃剂(IFR)的分解释放出大量NH3、H2O等不燃气体降低氧气浓度,PO2等气相淬灭剂与聚合物自由基反应,有效抑制燃烧的进行。②凝聚相阻燃机理,复合材料热解和APP分解时,磷酸和磷酸盐等酸性物质可以促进催化成炭,与协效阻燃剂(纳米硅酮粉)分解的硅氧烷反应,在材料表面可形成特殊的Si-O-P-C含硅无机陶瓷化致密残炭层,阻隔热氧交换,达到阻止燃烧的目的。③离子液体(IL)与膨胀型阻燃剂中的APP具有良好的协同阻燃效果,在燃烧过程中复合阻燃剂可以分解产生更多的含磷自由基,扑灭火焰中的氢自由基或氧自由基,更高效抑制燃烧的进行。④另外引入的PPO,与HIPS相容性好,提高HIPS的氧指数,从而提高了HIPS的可燃的难度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004071237260000071
    Figure BDA0004071237260000071
Patent Text Reader

Abstract

The application discloses a kind of high efficiency halogen-free flame-retardant high impact polystyrene (HIPS) material and preparation method thereof, belong to polystyrene material field.The application uses nano silicone powder as synergistic flame retardant and intumescent flame retardant to form composite flame retardant, and introduces ionic liquid, PPO (polyphenyl ether), reduces the use amount of intumescent flame retardant, greatly improves the efficiency of flame retardant, realizes the preparation of economic, efficient, halogen-free, low smoke, low toxicity, excellent mechanical property flame-retardant HIPS, and has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polystyrene materials, specifically relating to a high-efficiency, halogen-free, flame-retardant, high-impact polystyrene (HIPS) material and its preparation method. Background Technology

[0002] High-impact polystyrene (HIPS) is a thermoplastic produced by toughening it with elastomers. It consists of a rubber phase and a continuous polystyrene phase, thus possessing the advantages of polystyrene, such as easy processing, good insulation, good light stability, easy coloring, good rigidity, and chemical resistance, while also retaining the high toughness of the rubber phase. Therefore, HIPS is widely used in the automotive, computer, and furniture industries. For example, patent CN202011194465.7 discloses a method for preparing high-impact polystyrene, in which a flow modifier, butadiene rubber A (average molecular weight 150,000-200,000), and styrene-butadiene rubber B (average molecular weight 100,000-200,000) are dissolved in styrene monomers at a ratio of (0.5-2:1) to prepare a rubber solution, which is then transferred to a first-stage prepolymerization reactor. Polymerization is then carried out at 90-100℃ using an initiator, and when the conversion rate reaches 5-10%, the solution is transferred to a second-stage prepolymerization reactor. Patent CN202111660095.6 discloses a low dielectric high impact polystyrene resin and its preparation method. The polystyrene resin is prepared from the following components in parts by weight: 1000 parts of high impact polystyrene resin, 300-500 parts of muscovite, 100-200 parts of kaolin, 5-10 parts of coupling agent, 3-5 parts of antioxidant, and 10-20 parts of lubricant.

[0003] However, HIPS's low oxygen index (18%) makes it extremely flammable, and it also exhibits dripping during combustion, thus limiting its application in many situations. The flame retardants added to HIPS mainly include brominated flame retardants, phosphorus-based flame retardants, inorganic nano-flame retardants, and intumescent flame retardants, but these present problems such as environmental impact and reduced mechanical strength of HIPS: Brominated flame retardants have high flame retardant efficiency, but release toxic gases during combustion, seriously affecting the environment; phosphorus-based flame retardants have advantages such as low toxicity and low smoke, but are expensive; inorganic nano-flame retardant materials have advantages such as being green, safe, and widely available, but their efficiency needs improvement; intumescent flame retardants have high flame retardant efficiency, but require large amounts, affecting other properties of the material.

[0004] Silicon-based flame retardants possess advantages such as non-toxicity, smoke suppression, and environmental friendliness. They not only improve the flame retardant properties of composite materials but also effectively enhance the mechanical and processing properties of polymers. Silicon-based flame retardants can be mainly divided into organosilicon-based and inorganic silicon-based flame retardants. When organosilicon flame retardants melt under heat, they migrate through the gaps in the matrix to the surface of the composite material, forming a denser and more stable silicon-containing coke protective layer than conventional char layers. During combustion, inorganic silicon flame retardants primarily generate silica, forming an amorphous silicon protective layer on the surface of the composite material. Compared to inorganic silicon-based flame retardants, organosilicon-based flame retardants are characterized by better compatibility with polymers, achieving flame retardancy while improving the mechanical properties of the matrix material. Dai Yajie et al. studied the synergistic effect of montmorillonite (MMT), silicone powder (GM), and aluminum hydroxide (ATH) on the flame retardant properties of SEBS / PP composites and analyzed the char layer morphology using SEM. The results show that the flame retardant performance is significantly improved due to the synergistic effect of montmorillonite, silicone powder and aluminum hydroxide, the char layer structure is dense and the flame retardant effect is better.

[0005] In conclusion, the flame-retardant modification of HIPS will inevitably develop towards halogen-free, non-toxic, environmentally friendly, highly efficient, and synergistic effects. Therefore, it is urgent to find a new flame-retardant modification method to prepare novel, highly efficient flame retardants, which is the main development trend of flame-retardant HIPS in the future. Summary of the Invention

[0006] Objective of the Invention: To overcome the shortcomings of existing technologies, this invention provides a highly efficient, halogen-free, flame-retardant, high-impact polystyrene (HIPS) material and its preparation method. This invention uses nano-silicone powder as a synergistic flame retardant to form a composite flame retardant with an intumescent flame retardant, and introduces ionic liquids and PPO (polyphenylene oxide), achieving the economical, efficient, halogen-free, low-smoke, low-toxicity, and mechanically superior flame-retardant HIPS preparation, which has broad application value.

[0007] Technical solution: To achieve the above objectives, the technical solution of the present invention is as follows:

[0008] On the one hand, the present invention provides a high-efficiency halogen-free flame-retardant HIPS material, wherein the HIPS material includes HIPS, PPO, intumescent flame retardant, synergistic flame retardant, ionic liquid and aging aid.

[0009] Specifically, the HIPS material comprises the following raw materials in the following weight ratios: 60-80% HIPS, 10-20% PPO, 5-10% intumescent flame retardant, 3-5% synergistic flame retardant, 2-5% ionic liquid, and 0.5-1.5% aging aid.

[0010] More specifically, the HIPS is a modified PS (polystyrene) material with a melting temperature of 150-180℃ and contains 5-15% rubber components.

[0011] More specifically, the molecular weight of the PPO is 20,000-30,000.

[0012] More specifically, the intumescent flame retardant is a compound of pentaerythritol (PER), ammonium polyphosphate (APP), and melamine, in a ratio of 10-25:50-65:25-35.

[0013] More specifically, the ammonium polyphosphate (APP) contains 10-25% ammonium orthophosphate.

[0014] More specifically, the synergistic flame retardant is nano-silicone powder with an organosilicon content of ≥60%.

[0015] More specifically, the ionic liquid is [TBP][BF4] synthesized by anion exchange.

[0016] Due to the poor compatibility between intumescent flame retardants and substrates, ionic liquids, composed of anions and cations, are a new type of flame retardant material with unique design characteristics, low volatility, heat resistance, and low toxicity. Adding them in combination with intumescent flame retardants to polymers can effectively solve the compatibility problem and improve the flame retardancy of the polymer. This invention utilizes ionic liquid (IL) and ammonium polyphosphate (APP) to form a novel composite flame retardant (FR). IL and APP have a good synergistic flame retardant effect. During combustion, the composite flame retardant can decompose to generate more phosphorus-containing free radicals, extinguishing hydrogen or oxygen free radicals in the flame. Preferably, the mass ratio of IL:APP is 1:2, and the ionic liquid is synthesized via anion exchange [TBP][BF4].

[0017] In this invention, the synergistic flame retardant uses nano-silicone powder. When this organosilicon flame retardant material is heated and melted, it migrates to the surface of the composite material through the gaps in the matrix, forming a silicon-containing coke protective layer with a denser and more stable structure than a conventional char layer, thereby improving the flame retardant effect of the material.

[0018] The introduction of PPO into HIPS is primarily due to the good compatibility between PPO and HIPS. PPO has an oxygen index of 29 and is a self-extinguishing material, while the oxygen index of the flammable material HIPS is 17.8. The addition of PPO can improve the oxygen index of HIPS, thereby enhancing its flame retardant effect.

[0019] On the other hand, the present invention provides a method for preparing the above-mentioned high-efficiency halogen-free flame-retardant HIPS material, the method comprising the following steps:

[0020] (1) Dry mix HIPS, intumescent flame retardant, synergistic flame retardant, ionic liquid, PPO, and aging aid in a high-speed mixer for 3-5 minutes;

[0021] (2) The mixed raw materials are placed in a twin-screw extruder and granulated by melt extrusion.

[0022] Specifically, the HIPS material comprises the following raw materials in the following weight ratios: 60-80% HIPS, 10-20% PPO, 5-10% intumescent flame retardant, 3-5% synergistic flame retardant, 2-5% ionic liquid, and 0.5-1.5% aging aid.

[0023] More specifically, the HIPS is a modified PS (polystyrene) material with a melting temperature of 150-180℃ and contains 5-15% rubber components.

[0024] More specifically, the molecular weight of the PPO is 20,000-30,000.

[0025] More specifically, the intumescent flame retardant is a compound of pentaerythritol (PER), ammonium polyphosphate (APP), and melamine, in a ratio of 10-25:50-65:25-35.

[0026] More specifically, the ammonium polyphosphate (APP) contains 10-25% ammonium orthophosphate.

[0027] More specifically, the synergistic flame retardant is nano-silicone powder with an organosilicon content of ≥60%.

[0028] More specifically, the ionic liquid is [TBP][BF4] synthesized by anion exchange.

[0029] Specifically, the melting process in step (2) is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18MPa.

[0030] Beneficial effects: Compared with the prior art, the positive and beneficial effects of the present invention are as follows:

[0031] 1. This invention utilizes a novel flame-retardant system, specifically combining an intumescent flame retardant (IFR), a synergistic flame retardant, an ionic liquid, and PPO. The specific flame-retardant mechanism involves a combination of factors: ① Gas-phase flame-retardant mechanism: The decomposition of the intumescent flame retardant (IFR) releases a large amount of non-combustible gases such as NH3 and H2O, reducing the oxygen concentration. Gas-phase quenchers such as PO2 react with polymer free radicals, effectively inhibiting combustion. ② Condensed-phase flame-retardant mechanism: During the pyrolysis of the composite material and the decomposition of APP, acidic substances such as phosphoric acid and phosphates can promote catalytic char formation. These react with the siloxanes decomposed by the synergistic flame retardant (nano-silicone powder), forming a special Si-OPC silicon-containing inorganic ceramicized dense residual char layer on the material surface, blocking heat and oxygen exchange, thus preventing combustion. ③ The ionic liquid (IL) and the APP in the intumescent flame retardant have a good synergistic flame-retardant effect. During combustion, the composite flame retardant can decompose to generate more phosphorus-containing free radicals, extinguishing hydrogen or oxygen free radicals in the flame, and more effectively inhibiting combustion. ④ The additional PPO introduced has good compatibility with HIPS, increases the oxygen index of HIPS, and thus increases the difficulty of HIPS to become combustible.

[0032] 2. This invention reduces the amount of intumescent flame retardant used by combining materials, but greatly improves the flame retardant efficiency. By introducing PPO, ionic liquid and nano silicone powder, the compatibility between materials is greatly improved. While ensuring high flame retardancy, the mechanical properties are also greatly improved, and the appearance properties of the materials are also improved.

[0033] 3. The flame retardant used in this invention is an intumescent flame retardant. The additional synergistic flame retardants are nano silicone powder, ionic liquid and PPO. The decomposition products are substances such as NH3, CO2 and H2O. It is economical, smokeless and non-toxic.

[0034] 4. The preparation process of the high-efficiency halogen-free flame-retardant HIPS material proposed in this invention is simple and low in cost.

[0035] 5. The halogen-free flame-retardant HIPS material prepared by this invention has a non-crosslinked structure and can be recycled and reused as a general HIPS material without causing secondary pollution. Detailed Implementation

[0036] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are not intended to limit the present invention, but only to illustrate the present invention. Unless otherwise specified, the experimental methods used in the following embodiments are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.

[0037] Experimental materials: HIPS melt temperature 150-180℃, rubber content 5-15%; intumescent flame retardant is a compound of pentaerythritol (PER), ammonium polyphosphate (APP) and melamine, in a ratio of 10-25:50-65:25-35, with ammonium orthophosphate content in ammonium polyphosphate (APP) 10-25%; synergistic flame retardant is nano silicone powder, with organosilicon content ≥60%; ionic liquid is synthesized by anion exchange method [TBP][BF4]; PPO molecular weight is 20000-30000.

[0038] Example 1.

[0039] HIPS 64%, PPO 20%, intumescent flame retardant 8%, synergistic flame retardant 4%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0040] Example 2.

[0041] HIPS 69%, PPO 15%, intumescent flame retardant 8%, synergistic flame retardant 4%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0042] Example 3.

[0043] HIPS 74%, PPO 10%, intumescent flame retardant 8%, synergistic flame retardant 4%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0044] Example 4.

[0045] HIPS 84%, intumescent flame retardant 8%, synergistic flame retardant 4%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0046] Example 5.

[0047] HIPS 68%, PPO 15%, intumescent flame retardant 8%, synergistic flame retardant 5%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0048] Example 6.

[0049] HIPS 70%, PPO 15%, intumescent flame retardant 8%, synergistic flame retardant 3%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0050] Example 7.

[0051] HIPS 73%, PPO 15%, intumescent flame retardant 8%, ionic liquid 3%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0052] Example 8.

[0053] HIPS 67%, PPO 15%, intumescent flame retardant 8%, synergistic flame retardant 4%, ionic liquid 5%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0054] Example 9.

[0055] HIPS 70%, PPO 15%, intumescent flame retardant 8%, synergistic flame retardant 4%, ionic liquid 2%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0056] Example 10.

[0057] HIPS 72%, PPO 15%, intumescent flame retardant 8%, synergistic flame retardant 4%, and aging aid 1% are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.

[0058] Experimental Example 1. Performance Evaluation Methods and Implementation Standards

[0059] The granulated particle material prepared according to the above embodiment is dried in a forced-air oven at 60°C for 2-3 hours before being injection molded on an injection molding machine to prepare a sample.

[0060] Tensile properties were tested according to ISO 527-2, with a specimen size of 150*10*4mm and a tensile speed of 50mm / min; bending properties were tested according to ISO 178, with a specimen size of 80*10*4mm, a bending speed of 2mm / min, and a span of 64mm; impact strength of simply supported beams was tested according to ISO 179, with a specimen size of 80*6*4mm and a notch depth of one-third of the specimen thickness; limiting oxygen index (LOI) was measured using a limiting oxygen indexer.

[0061] The formulation and test results of the samples are shown in Table 1 below:

[0062] Table 1: Examples and Material Properties

[0063]

[0064] As can be seen from Examples 1-4 in Table 1, with the increase of PPO addition, the limiting oxygen index (LOI) of the material increases, and the strength also improves. This is because PPO has good compatibility with HIPS, and the limiting oxygen index of PPO is much higher than that of HIPS. Through the tight entanglement of PPO molecules with HIPS, the limiting oxygen index (LOI) of the material is greatly improved, and the strength of the material is also improved. A comparison of Examples 2, 5, 6 and Example 7 shows that the addition of the synergistic flame retardant (nano-silicone powder) not only greatly improves the mechanical properties of the material, but also increases the limiting oxygen index (LOI) and significantly improves the flame retardant effect. This is because the addition of nano-silicone powder greatly improves the compatibility of the intumescent flame retardant with the composite material. Furthermore, the composite material... During the pyrolysis of the material and the decomposition of APP, acidic substances such as phosphoric acid and phosphates can promote catalytic char formation. This char reacts with the siloxanes decomposed by the synergistic flame retardant (nano silicone powder) to form a special Si-OPC silicon-containing inorganic ceramic dense residual char layer on the material surface. This layer blocks heat and oxygen exchange, achieving the purpose of effectively preventing combustion. A comparison of Examples 2, 8, and 9 with Example 10 shows that the addition of ionic liquid significantly increases the limiting oxygen index (LOI) and has a better flame retardant effect. This is because the ionic liquid (IL) and the APP in the intumescent flame retardant have a good synergistic flame retardant effect. During combustion, the composite flame retardant can decompose to generate more phosphorus-containing free radicals, extinguishing hydrogen or oxygen free radicals in the flame and more effectively inhibiting combustion.

[0065] Therefore, the flame retardant system of this invention is based on an intumescent flame retardant system, combined with the use of synergistic flame retardants (nano silicone powder) and ionic liquids, and introduces PPO to improve the flame retardant effect of the material from multiple aspects such as the gas phase, condensed phase and the material itself. Combined with the improvement of material compatibility, it is not only novel in approach and flexible in design, but also highly efficient in flame retardancy, smokeless, non-toxic, non-polluting, and with excellent mechanical properties.

[0066] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-efficiency halogen-free flame-retardant HIPS material, characterized in that: The HIPS material includes HIPS, PPO, intumescent flame retardant, synergistic flame retardant, ionic liquid, and aging aid; The HIPS material comprises the following raw materials in the following weight ratios: HIPS 60-80%, PPO 10-20%, intumescent flame retardant 5-10%, synergistic flame retardant 3-5%, ionic liquid 2-5%, and aging aid 0.5-1.5%; The sum of the contents of all components is 100%; The intumescent flame retardant is a compound of pentaerythritol, ammonium polyphosphate and melamine, in a ratio of 10-25:50-65:25-35; The aforementioned synergistic flame retardant is nano-silicone powder with an organosilicon content of ≥60%; The ionic liquid described is synthesized via anion exchange [TBP][BF4].

2. The HIPS material according to claim 1, characterized in that: The HIPS has a melting temperature of 150-180℃ and contains 5-15% rubber.

3. The HIPS material according to claim 2, characterized in that: The molecular weight of the PPO is 20,000-30,000.

4. The HIPS material according to claim 3, characterized in that: The content of ammonium orthophosphate in the ammonium polyphosphate is 10-25%.

5. A method for preparing the HIPS material according to any one of claims 1-4, characterized in that: The method includes the following steps: (1) Dry mix HIPS, intumescent flame retardant, synergistic flame retardant, ionic liquid, PPO, and aging aid in a high-speed mixer for 3-5 minutes; (2) The mixed raw materials are placed in a twin-screw extruder and granulated by melt extrusion.

6. The preparation method according to claim 5, characterized in that: The melting process in step (2) is as follows: Zone 1 210-220℃, Zone 2 210-220℃, Zone 3 220-230℃, Zone 4 220-230℃, Zone 5 225-235℃, Zone 6 235-245℃, Zone 7 240-250℃, Zone 8 240-250℃, Zone 9 235-245℃, Zone 10 235-245℃; residence time is 1-2 minutes, and pressure is 12-18MPa.

Citation Information

Patent Citations

  • Preparation method of high-impact polystyrene

    CN112321773A

  • Low-dielectric high-impact polystyrene resin and preparation method thereof

    CN114213796A

  • High-fluidity environmental protection halogen-free flame-retardant HIPS composite material and its preparation method

    CN102477189A

  • Flame-retardant aging-resistant PPO-HIPS polymer alloy and preparation method thereof

    CN105199364A